Preparation of anatase TiO2 nanorods with high aspect ratio for high-performance dye-sensitized solar cells. (January 2016) - Tang, Ying; Wang, Chen; Hu, Yajing; Huang, Lu; Fu, Jianxun; Yang, Weiguang
Abstract: Due to offering a direct conduction pathway and fast electron transport, 1D nanostructures play an important role in improving charge collection efficiency in dye-sensitized solar cells (DSSCs). The anatase TiO2 nanorods with different aspect ratios between 3.2 and 6.3 were obtained by controlling reaction time for DSSCs. As their aspect ratios increased, more dye was adsorbed on the anatase TiO2 nanorods film. A promising power conversion efficiency of 7.51% was obtained for the anatase TiO2 nanorods with the biggest aspect ratio of 6.3. Highlights: Preparation of single-crystalline anatase TiO2 nanorods with high aspect ratio. Different aspect ratios can be controlled and obtained. Their dye loadings and efficiencies increase as their aspect ratios increasing. A promising power conversion efficiency of 7.51% was obtained for the anatase TiO2 nanorods with the biggest aspect ratio of 6.3.